Analisis Tindak Tutur Ilokusi Akun Baksosapi.gapakemicin dalam Unggahan di Instagram (Suatu Analisis Pragmatik) - Melani, Melly Vila; Yudi Utomo, Asep Purwo (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This study focuses on the use of speech act in pragmatic mainly focused on illocution act on Baksosapi.gapakemicin instagram account. This research used descriptive method by observing research objects. The data resource in this research is illocution act on Baksosapi.gapakemicin instagram account which are straightforward and meaningful language. Austin's theory was used to assess and analyze the situation, representative, directive, expressive, commissive, and directive in the presence of evidence of uploads and analyzed from Searle. The result of this research showed that speech act which is often used in Baksosapi.gapakemicin instagram account is illocution act, although it tends to show joke or unclear text. However, this account has a great influence to reader dealing with something that has been written in the upload.